OUT-MIGRATION IN INDONESIA AND ITS DETERMINING FACTORS - Farit Firdaus Lutfiantara; Muhammad Arif (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of economic factors on out-migration in Indonesia, with a focus on poverty, wage levels, labor force participation, and unemployment rates. The research utilizes panel data from 34 provinces across three observation periods—2010, 2015, and 2020—employing a quantitative approach through panel data regression. The Fixed Effects Model (FEM) is determined as the most appropriate model based on the Chow and Hausman tests. The estimation results indicate that poverty and labor force size have a positive effect on out-migration. Meanwhile, wage levels and unemployment rates do not show a significant impact. These findings suggest that regional economic disparities and labor market pressures drive population mobility to other areas. Therefore, policies focusing on reducing regional inequality, expanding employment opportunities, and strengthening local economic bases are needed. This study contributes to migration research through the use of nationally scaled panel data, which enables a more structured explanation of the spatial and temporal dynamics of out-migration in Indonesia.